The psychophysical assessment of odor valence: does an anchor stimulus influence the hedonic evaluation of odors? - Clepce, Marion; Neumann, Konrad; Martus, Peter; Nitsch, Marie; Wielopolski, Jan; Koch, Anna Maria; Kornhuber, Johannes; Reich, Karin; Thürauf, Norbert (Chemical Senses, 2014)
Olfactory stimuli are experienced primarily in terms of their hedonic tone and the assessment of olfactory hedonic estimates is a prevalent task in scientific and industrial contexts. However, measuring conditions are poorly standardized. Our study aims to fill this gap, focusing on the influence of anchor stimuli on olfactory hedonic evaluations, frequency of anchor presentation, and temporal stability of results. In n = 31 subjects, hedonic estimates for the 16 odors of the Sniffin' Sticks identification task were assessed on a visual analog rating scale under 4 measuring conditions (nonanchor, pleasant anchor, neutral anchor, unpleasant anchor). To test for stability over time, n = 10 subjects were reassessed 2, 4, and 6 months after original testing. To analyze for possible effects of single versus repeated anchor presentation, n = 15 subjects were retested 2 months after the original session in a multiple anchor presentation format. Statistical analysis revealed significant differences between the 4 anchor conditions, thus highlighting the necessity of specifying assessment methods in scientific research. No significant differences between timepoints were observed, indicating a high temporal stability of olfactory hedonic evaluations, especially from timepoint T2 onward. No overall significant effects of single versus multiple anchor presentation were detected. Findings might help to further standardize testing procedures.
EVALuna2:23574